Human Bone Remains from Krusza Zamkowa. Results of Anthropological Examinations - Piontek, Janusz; Mucha, Elżbieta (Anthropological Review, 1985)
The osteological material originates from La Tène period from crematory and skeletal graves. Morphological and paleodemographical characteristics are given.